Digital economy and urban insurance demand: empirical evidence from 289 cities in China - Liang, Mengyadi (Frontiers in Human Dynamics, 2025)
Against the backdrop of the digital economy profoundly leading the modernization of industrial systems and structures, this study focuses on the impact mechanism of the digital economy on urban insurance demand. Based on panel data from 289 cities in China between 2007 and 2022, a two-way fixed effects model is constructed, and empirical research is conducted using an instrumental variable approach and heterogeneity analysis. The findings are as follows: First, the direct driving effect of the digital economy. The digital economy has a significant positive impact on total insurance demand (TID), property insurance demand (PID), and health insurance demand (HID), with its effect on HID being approximately 1.53 times that on PID, reflecting the more prominent role of health protection demand under the influence of the digital economy. Second, the reinforcing logic of moderating and mediating effects. Economic development level (EDL) significantly strengthens the driving effect of the digital economy on PID by improving digital infrastructure and diversifying demand; human capital level (HCL) comprehensively amplifies the digital driving effect on insurance demand by enhancing the digital adaptation capacity of both supply and demand sides. Meanwhile, the digital economy promotes insurance demand by boosting consumption expenditure (CE). Third, regional heterogeneity characteristics. The impact of the digital economy on insurance demand exhibits a spatial pattern of “stronger in the north than in the south, and stronger in inland areas than in coastal areas.” This study provides mechanistic insights and policy optimization pathways to address the regional disparities in the synergistic development of the digital economy and urban insurance.